Diagnóstico das encefalites herpéticas em bovinos - Erica Azevedo Costa (2008)
A study about bovine herpetic encephalitis was performed in a period during November 2004 to February 2006 in the state of Minas Gerais, Brazil. Four hundred and thirteen (413) samples of the central nervoussystem (CNS) of bovines which died presenting neurological signs were analyzed and sent to the Instituto Mineiro de Agropecuária (IMA) for rabies virus detection and tested negative. These samples were given by IMAs Animal Health Laboratory (Laboratório de Saúde Animal LSA) for the detection, through PCR assays, of the following herpesviruses: bovine herpesvirus 1 (BHV-1), bovine herpesvirus 4 (BHV-4), bovine herpesvirus 5 (BHV-5), swine herpesvirus 1 (SHV-1), ovine herpesvirus 2 (OHV-2) andalcelaphine herpesvirus 1 (AHV-1). The data referring to the origin, the animal identification, herd, macroscopic and microscopic diagnosis of the CNS and clinical signs observed by independent veterinarians and official organs during the material collection in the field was filed, revised and subsequently evaluated. There was a high occurrence of BHV-5 in the 413 samples of CNS, with 188 (45.5%) positive samples, and only one (0.2%) sample positive for the BHV-1. The SHV-1 was detected in 5 (1.2%) samples whilst the OVH-2 and BHV-4 were detected in 17 (4.1%) and 14 (3.4%) samples respectively. The AHV-1 was not detected in any of the CNS samples analyzed. The histopathological lesions found in the CNS where the herpesviruses were detected were classified as non-suppurative meningoencephalitis. The course of the neurological disease presented by bovines infected with any kind of herpesvirus varied between 1 to 22 days and the age of the animals ranged between 2 months and 18 years old. The CNS samples derived from 173 municipalities and 106 (61.2%) presented positive samples for one of the herpesviruses. All ten (10) administrative regions of Minas Gerais were affected by the herpesviruses showing that the viruses are disseminated throughout the whole state of Minas Gerais. Therefore, it is obvious the necessity to include the herpesviruses tests, particularly the BHV-5, in the differential diagnostic, to rule out other diseases which affect the bovines CNS. In Minas Gerais, the collected samples are normally tested for the rabies virus only